2015
DOI: 10.5301/jabfm.5000201
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Silicate and Calcium Hydroxide Materials for Pulp Capping: Biointeractivity, Porosity, Solubility and Bioactivity of Current Formulations

Abstract: calcium silicate-based cements are biointeractive (ion-releasing) bioactive (apatite-forming) functional biomaterials. The high rate of calcium release and the fast formation of apatite may well explain the role of calcium silicate biomaterials as scaffold to induce new dentin bridge formation and clinical healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
264
1
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(302 citation statements)
references
References 47 publications
20
264
1
17
Order By: Relevance
“…Islam et al [29] also observed low solubility levels for white PC, in comparison with MTA. On the other hand, Gandolfi et al [33,37,38] showed high solubility levels for ProRoot MTA; moreover, they attributed the high solubility to the long setting time exhibited by the material. These differences may be attributed to the type of PC evaluated in the present study, and to the long setting time (3 times the initial setting time) applied before the solubility test.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Islam et al [29] also observed low solubility levels for white PC, in comparison with MTA. On the other hand, Gandolfi et al [33,37,38] showed high solubility levels for ProRoot MTA; moreover, they attributed the high solubility to the long setting time exhibited by the material. These differences may be attributed to the type of PC evaluated in the present study, and to the long setting time (3 times the initial setting time) applied before the solubility test.…”
Section: Discussionmentioning
confidence: 95%
“…Studies showed that the amount of leached calcium decreased with time for calcium silicate materials such as ProRoot MTA, Dycal and TheraCal [37], MTAAngelus [39], and light-cure resin-modified calcium silicate cement [33]. Calcium silicate materials (ProRoot MTA, MTAAngelus, MTA Plus, Biodentine, Tech Biosealer capping, and TheraCal) release more calcium than pulp-capping calcium hydroxide materials (Calxyl, Dycal, Life, and Lime-Lite) [38]. Gandolfi et al [41] showed that ProRoot MTA, MTAAngelus, and Tech Biosealer root-end act as sources of hydroxyl and calcium ions and contribute to creating a calciumrich alkaline environment.…”
Section: Discussionmentioning
confidence: 99%
“…Gandolfi et al reported high releases of calcium and hydroxyl ions in ProRoot MTA and Tech Biosealer Root End 17. In addition, Tech Biosealer Capping released greater amounts of calcium compared to ProRoot MTA, Pulpdent and Dycal 44. Hakki et al evaluated the response of cementoblasts to Tech Biosealer and reported a significant decrease in cell viability 18.…”
Section: Discussionmentioning
confidence: 99%
“…Here the calcium release from TheraCal LC was significantly more than Dycal. 6 Yet another similar study by Chaudari et al in 2016, Septocal LC was tested as another experimental group along with TheraCal LC. The study reported better calcium releasing property of both the cements.…”
Section: Discussionmentioning
confidence: 99%
“…Though this material has adequate calcium release, it is hydrolytically unstable and is moisture sensitive. 6 Alternate materials such as MTA, white Portland cements are self-setting hydrophilic calcium silicate cements. They exhibit lesser pulpal necrosis, lesser inflammation, more and faster deposition of hard tissue barrier that is more homogenous and complete.…”
Section: Introductionmentioning
confidence: 99%